WEB-BASED EMPLOYEE RECRUITMENT INFORMATION SYSTEM DESIGN AT PT SEKAR PUTRA DAERAH - Pradana, Jihad Rengga Putra; Chotijah, Umi (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
Along with the rapid development of information technology, companies are required to adapt in various operational aspects, including the employee recruitment process. PT Sekar Putra Daerah, as a continuously growing company, faces challenges in managing its recruitment process, which is still carried out conventionally—consuming considerable time and resources. Manual processes are prone to human error, document loss, and difficulties in tracking application statuses. To address these issues, a web-based employee recruitment information system was developed. This study aims to design, develop, and implement a digital platform that automates the entire recruitment workflow—from job postings by the administrator, registration and application submission by applicants, to the selection process and notification of application status. The system development method used is the Waterfall model, which includes the stages of requirements analysis, system design, implementation, testing, and maintenance. The result of this study is a functional web application with two main access roles: administrator and applicant. Administrators can manage job postings, filter incoming applications, and update applicant status, while applicants can create accounts, view available job openings, submit applications, and monitor their application status in real time through a dashboard and notifications. The implementation of this system is expected to improve the efficiency, transparency, and effectiveness of the recruitment process at PT Sekar Putra Daerah, as well as provide a better experience for prospective employees.